Science Process skills analysis in children aged 4-6 years at Santa Lusia Medan Kindergarten - Nurmaniah Nurmaniah; Risa Sianturi (BIRCU, 2020)
This study examined the skills of science process in children aged 4-6 years and became the formulation of this research, the problem is how science process skills of children aged 4-5 years and 5-6 years in Santa Lusia Kindergarten Medan. This research aimed to find out how science process skills of children aged 4-6 years in Santa Lusia Kindergarten Medan. The source of the research data was from teachers in kindergarten and the subject is in learning. Based on the initial survey, the research subject in this study was 20 children with 6 children as sample. Children aged 4-5 3 children consisting of 2 boys and 1 girl and for ages 5-6 3 children consisting of 2 boys and 1 girl that divided into 3 categories, which is a child who has Active, medium and low science process skills. The research methods used qualitative descriptive. The data collection techniques were done with an in-depth observation and interview to the resource teacher, the teachers of the creative classroom Santa Lusia Kindergarten Medan. Data was analyzed by data collection, data reduction, data presentation, withdrawal of conclusions and verification. The results showed that the skills of the science process demonstrated by children aged 4-6 years was medium category. Because of the 20 children who were observed only 5 children who had active skills of science processes and 12 children had medium science skills that last there are 3 children who belong to the low science process..